Pengaruh POC Fermentasi Limbah Cair Tahu, Kipahit (Tithonia diversifolia), Bonggol Pisang Terhadap Pertumbuhan dan Hasil Tanaman Lobak (Raphanus sativus L.) - Catur Setiyani; Maria Marina Herawati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aimed to analyze the effect of applying liquid organic fertilizer (POC) derived from a combination of three materials on the growth and yield of radish plants (Raphanus sativus L.). The research utilized a randomized block design (RBD) with five treatment doses, namely TBT0 (control), TBT100 (100 ml/plant), TBT200 (200 ml/plant), TBT300 (300 ml/plant), and TBT400 (400 ml/plant). The results showed that applying POC at a dose of 200 ml/plant (TBT200) produced the highest average number of leaves (29.90 leaves) and the highest radish bulb weight (483.62 grams). However, the application of POC to leaf area, chlorophyll content, and dry leaf weight exhibited a pattern without significant changes among the treatments. Soil nutrient content also decreased as it was utilized by the plants during growth. In conclusion, the application of POC doses made from liquid tofu waste, kipahit (Tithonia diversifolia), and banana stems significantly influenced the number of leaves, fresh leaf weight, and productivity of radish plants. However, POC application did not significantly affect leaf area, chlorophyll content, or dry leaf weight. Keywords: Banana Stem, Kipahit (Tithonia diversifolia), Liquid Tofu Waste, POC, Radish Plants